EMI teacher development in the internationalization at home process at university - Pletsch, Cleonice (2021)
This research paper aimed to investigate the Didactic Sequence (DS) model (DOLZ, NOVERRAZ AND SCHNEUWLY, 2004) potential, combined with the Oral Exposition Genre TED Talk (ANDERSON, 2016), for English as a Medium of Instruction (EMI). A teacher development course for professors and postgraduate students was put into practice observing the Design-Based Research methodology from the qualitative research paradigm to plan, test and evaluate a DS for developing language capacities (STUTZ & CRISTOVÃO, 2011; CRISTOVÃO, 2013; MAGALHÃES & CRISTOVÃO, 2018) in Higher Education (HE). Based on Socio-discursive Interactionism fundamentals (BRONCKART, 2006), English as a Lingua Franca (CANAGARAJAH, 2006; VIÉGAS, 2016; SANTOS & SIQUEIRA, 2019) and the global citizenship perspectives, the study, in the area of applied linguistics, was conducted considering the increasing area of Internationalization at Home (IaH) and EMI in HE, especially in the local context. The perception of oral performance in English as a barrier for higher educators was decisive in implementing the course. Results were positive in terms of the potential of the proposed DS model to develop language capacities and serve as support for EMI classes in HE. Discursive capacities related to organization and content were evidenced in the final product, as well as a general improvement of other language capacities. It was demonstrated that the more actions to back up faculty members are put into practice, the more EMI can be implemented, fostering IaH in the local community.